Minimization of a supermodular functions over a relatively complemented finite lattice - Salazar, Nelson Aragonés (2017)
This work presents two discarding principles to solve the problem of the minimization of a supermodular function over a relatively complemented finite lattice. This result generalizes the one presented in [1] for the case of a supermodular function defined in the class of subsets of a given finite set.